Legitimasi, Efektivitas dan Akuntabilitas G-20 Sebagai Klub Eksklusif dalam Pembentukan Tata Kelola Ekonomi Global - Yulius Purwadi Hermawan (Jurnal Ilmiah Hubungan Internasional, 2012)
This paper examines the modalities and challenges the G-20 as an exclusive club in running inclusive mandate to tackle the global financial crisis and the global financial structure to form a robust and resilient to the financial crisis. A limited number of conceptually does provide an  opportunity for the club to prove its effectiveness in addressing the global financial crisis. However, this paper argues that the measure of success of the G-20 not only in its ability to address the needs of their members effectively, but also its ability to provide benefits to all the nations of the world, including those who are not members of the club.Keywords : G-20, Global Governance, Club Theory